Playing with things : the archaeology, anthropology and ethnography of human-object interactions in Atlantic Scotland - Wilson, Graeme, (Archaeopress Publishing Ltd, 2018)
Represents a reappraisal of the relationship between play - an activity which is most often understood in terms of something 'set apart' - and everyday life. Via a series of archaeological, anthropological and ethnographic investigations, it leads towards the conclusion that play is not in fact so separate as is often assumed.